Heart-Specific Immune Responses in an Animal Model of Autoimmune-Related Myocarditis Mitigated by an Immunoproteasome Inhibitor and Genetic Ablation. Issue 23 (9th June 2020) - Bockstahler, Mariella; Fischer, Andrea; Goetzke, Carl Christoph; Neumaier, Hannah Louise; Sauter, Martina; Kespohl, Meike; Müller, Anna-Maria; Meckes, Christin; Salbach, Christian; Schenk, Mirjam; Heuser, Arnd; Landmesser, Ulf; et al.
Abstract : Background: Immune checkpoint inhibitor (ICI) therapy is often accompanied by immune-related pathology, with an increasing occurrence of high-risk ICI-related myocarditis. Understanding the mechanisms involved in this side effect could enable the development of management strategies. In mouse models, immune checkpoints, such as PD-1 (programmed cell death protein 1), control the threshold of self-antigen responses directed against cardiac TnI (troponin I). We aimed to identify how the immunoproteasome, the main proteolytic machinery in immune cells harboring 3 distinct protease activities in the LMP2 (low-molecular-weight protein 2), LMP7 (low-molecular-weight protein 7), and MECL1 (multicatalytic endopeptidase complex subunit 1) subunit, affects TnI-directed autoimmune pathology of the heart. Methods: TnI-directed autoimmune myocarditis (TnI-AM), a CD4 + T-cell–mediated disease, was induced in mice lacking all 3 immunoproteasome subunits (triple-ip −/− ) or lacking either the gene encoding LMP2 and LMP7 by immunization with a cardiac TnI peptide. Alternatively, before induction of TnI-AM or after establishment of autoimmune myocarditis, mice were treated with the immunoproteasome inhibitor ONX 0914. Immune parameters defining heart-specific autoimmunity were investigated in experimental TnI-AM and in 2 cases of ICI-related myocarditis. Results: All immunoproteasome-deficient strains showed mitigated autoimmune-related cardiac pathology with less inflammation, lower proinflammatory and chemotactic cytokines, less interleukin-17 production, and reduced fibrosis formation. Protection from TnI-directed autoimmune heart pathology with improved cardiac function in LMP7 −/− mice involved a changed balance between effector and regulatory CD4 + T cells in the spleen, with CD4 + T cells from LMP7 − /− mice showing a higher expression of inhibitory PD-1 molecules. Blocked immunoproteasome proteolysis, by treatment of TLR2 (Toll-like receptor 2)–engaged and TLR7 (Toll-like receptor 7)/TLR8 (Toll-like receptor 8)–engaged CD14 + monocytes with ONX 0914, diminished proinflammatory cytokine responses, thereby reducing the boost for the expansion of self-reactive CD4 + T cells. Correspondingly, in mice, ONX 0914 treatment reversed cardiac autoimmune pathology, preventing the induction and progression of TnI-AM when self-reactive CD4 + T cells were primed. The autoimmune signature during experimental TnI-AM, with high immunoproteasome expression, immunoglobulin G deposition, interleukin-17 production in heart tissue, and TnI-directed humoral autoimmune responses, was also present in 2 cases of ICI-related myocarditis, demonstrating the activation of heart-specific autoimmune reactions by ICI therapy. Conclusions: By reversing heart-specific autoimmune responses, immunoproteasome inhibitors applied to a mouse model demonstrate their potential to aid in the management of autoimmune myocarditis in humans, possibly including patients with ICI-related heart-specific autoimmunity. Abstract : Supplemental Digital Content is available in the text.